Re-evaluating post-conviction disclosure: A case for ‘better late than never' - Greenwood, Holly (International journal of law, crime and justice, 2019)
The recent instances of fundamental failings in pre-trial disclosure should also place systemic procedures for post-conviction disclosure firmly in the spotlight. Drawing on the authors' experience of working on university miscarriage of justice projects, this paper will argue that the UK Supreme Court decision in R v Nunn must be revisited to strengthen the duty of disclosure of material post-trial, and to provide sanctions for authorities that fail to comply. In the current climate of austerity, there is increasing reliance on student projects and other similar organisations to assist appellants post-conviction; it is necessary to determine what their role should be and what rights they might have to access material on behalf of defendants. The article concludes by suggesting that fairness demands for consideration to be given to proposals in the "Open Justice Charter," which is a document drafted by several academics and practitioners in the field of criminal appeals.